Diffusion and usage patterns of Internet services in the European Union - José Manuel Ortega Egea; Manuel Recio Menéndez; María Victoria Román González (Information Research: An International Electronic Journal)
Introduction. This paper offers an investigation of European citizens' adoption and use of Internet-related technologies. European citizens are classified according to their Internet usage patterns. Next, the demographic and behavioural profiles of the identified groups are thoroughly examined, which clarifies citizens' Internet-related behaviour and how external variables are related to Internet uses. Method. Telephone survey, using a random method, in order to guarantee the representativity of each national sample for its universe. Citizens from all European countries (EU-15) were surveyed about their Internet usage patterns. Analysis. Two-Step Cluster Analysis has been applied, to identify the different groups of European Internet users. Discriminant and Correspondence Analysis have been respectively applied to assess the internal and external validity of the identified segments. The statistical package SPSS v11.5 was employed for the empirical analyses. Results. Four segments of European Internet users have been identified: Laggards, Confused and Adverse, Advanced Users, Followers and Non-Internet Users. The behavioural and demographic profiles of the previously identified segments are examined. Next, the internal and external validity of the clusters is assessed. Conclusion. The identified Internet user segments show clear differences with regard to country, sex, occupation, education and location. These results confirm the existence of sociodemographic entry barriers to the use of digital services. Such barriers may to the development and widening of a digital divide among European citizens.